Formulation And Evaluation Of Ketotifen Fumarate-Loaded Nanoparticles For Enhanced Transdermal Drug Delivery - Kumar, Girijesk; S, Rajasekaran. (Journal of Neonatal Surgery, 2025)
Ketotifen Fumarate, a non-competitive H1-receptor antagonist, is widely used for the prophylactic treatment of allergic conditions such as asthma, rhinitis, and chronic urticaria. However, its clinical effectiveness is limited by low oral bioavailability ( 50%), short plasma half-life, and significant first-pass metabolism. This study aimed to overcome these limitations by formulating and evaluating lipid-based nanoparticles for potential transdermal delivery. Nanoparticles were prepared using soyalecithin and ethanol via the emulsification–solvent diffusion method, incorporating propylene glycol to enhance skin permeability. The formulations were characterized for particle size, zeta potential, encapsulation efficiency, swelling index, and in vitro drug release. Among the eight formulations (KFN-1 to KFN-8), KFN-6 showed optimal characteristics, including small particle size (93.47 µm), high zeta potential (27.16 mV), and encapsulation efficiency (89.38%). In vitro release studies indicated a sustained release profile, with Korsmeyer-Peppas kinetics suggesting a non-Fickian diffusion mechanism. The findings support the potential of lipid-based nanoparticles as an effective transdermal delivery system for improving the therapeutic performance of Ketotifen Fumarate